ANÁLISE PROBABILÍSTICA DO GERENCIAMENTO DA CONGESTÃO EM MERCADOS DE ENERGIA ELÉTRICA - Rodrigues, Anselmo Barbosa (2003)
The restructuring of the electricity industry has caused an increase in the number of commercial transactions carried out in energy markets. These transactions are defined by market forces without considering the operational constraints of the transmission system. As a consequence, there are transactions that cause congestion in the transmission network, that means, violations of operational limits in one or more circuits of the transmission system. In this way, the congestion in the transmission system must be eliminated by using corrective actions, such as redispatch of generation/transactions and operation of control flow devices, to avoid cascading outages with uncontrolled loss of load. Currently, the majority of methodologies used in congestion management are based on deterministic models. It has been justified because of the complexity associated with the application of probabilistic models in generation/transmission systems. Nevertheless, some models have been developed to carry out probabilistic analysis of the congestion management. Usually, they are based on the Monte Carlo Method with nonsequential simulation and they only include bilateral transactions. However, multilateral transactions are also essential for the existence of the energy markets. The multilateral transactions reduce the financial risks associated with commercial transactions and allow the customers to have access to the energy providers. Additionally by ignoring multilateral transactions, the existing probabilistic models for the congestion management include only not-free-cost corrective actions, such as generation redispatch and transaction curtailments. On the other hand, free-cost corrective actions, such as phase shifting transformers and FACTS devices, can provide low cost solutions to eliminate congestion in interconnections of the transmission system. This condition is caused by the delay in carrying out reinforcements in the transmission systems due to financial and environmental constraints. Finally, it must be noted that only probabilistic indices based in expected values are evaluated by the probabilistic models of congestion management. However, system operators have difficulty in interpreting probabilistic indices based only in expected values. Therefore, it is necessary to develop new indices to carry out probabilistic analysis of congestion management. These new indices must consider traditionally accepted operational criteria and they must be easily interpreted by the system operators. This research has as its objective the development of models and techniques to carry out the probabilistic analysis of congestion management. The proposed models and techniques consider the following aspects associated with congestion management: the modeling of multilateral transactions, phase shifting transformers and the definition of Well-Being Indices to assess the reliability of the commercial transactions. These indices, allow the establishment of a link between the operational criteria traditionally used and the stochastic model of the electrical network. The models and indices, proposed in this research, have been based on the Monte Carlo Method with non-sequential simulation and in the linearized optimal power flow. The optimal power flow problems associated with the congestion management have been solved using the Primal-Dual Interior-Point Method. The practical application and the validation of the models and indices proposed in this research have been carried out in two systems: the IEEE System, proposed in 1996, for Reliability Studies. The main conclusions obtained with the application of the proposed models and techniques in the IEEE system are: multilateral congestion management can improve the reliability of commercial transactions, load profiles have significant effects on the Well-Being indices of the transactions, the base case condition has great impact in the Well-Being indices associated with a set of transactions and the operation of phase-shifting transformers and can decrease significantly the curtailments in the commercial transactions.